Recovery of Low-Grade Heat (Heat Waste) from a Cogeneration Unit for Woodchips Drying: Energy and Economic Analyses - Tilia Dahou; Patrick Dutournié; Lionel Limousy; Simona Bennici; Nicolas Perea (Energies, 2019)
The aim of this paper is to improve the operating share of a biomass cogeneration unit by using unavoidable heat waste heat recovered from a district network heating used for drying woody biomass’ return water (law-grade temperature heat). The optimal operating conditions of a drying unit added to the system were estimated from an energy and a financial point of view, applying four objective functions (drying time, energy consumption, energy balance, and financial performance of the cogeneration unit). An experimental design methodology used heat for the implementation of these functions and to obtain an operating chart. Numerical modelling was performed to develop a simulation tool able to illustrate the unsteady operations able to take into account the available waste heat. Surprisingly, the model shows that the right strategy to increase the financial gain is to produce more warm water than necessary and to consequently dispose higher quantities of unavoidable heat in the network’s return water, which heat up the drying air at a higher temperature. This result contrasts with the current approaches of setting-up cogeneration units that are based on the minimization of the heat production.